Análise multitemporal da variação da linha de costa em praias do município de Marapanim, Nordeste do Pará - BAÍA, Lohan Barbosa (2018)
The morphological changes in shorelines result mainly from changes in sea level due to astronomical, tectonic, climatic and meteoceanographic phenomena. These natural phenomena, related to coastal problems on the coast, can result in coastal regions affected by erosive and accretive processes. The analysis of variations in the coastlines through multitemporal images of a certain area of study, allows the identification of these processes, in an evolutionary scale. The objective of this work was to verify and evaluate the changes in the coastline of the municipality of Marapanim between the years 1988 to 2016 in the beaches of Santa Maria, Marudá and Crispim by means of images of the Landsat satellite. For this work the coastlines were digitized in the reference years, and an extension of the ArcGis software that performs statistical calculations (DSAS) from transects originally elaborated from a baseline was used, making available as data products of spatial amplitude and annual rate of variation of coastline positioning. The results indicated that the beach of Santa Maria is in a state of sedimentary equilibrium, presenting extreme values of accretion, varying from 3.89 to -1.23 m / year; the beach of Marudá is in accretion presenting extreme values of accretion, varying from 8.87 to -1.61 m / year; and the beach of Crispim is also in the process of accretion presenting extreme values of accretion, varying from 40.91 to -9.82 m / year, but with the rate of accretion decreasing. Climatic, physical phenomena and anthropic impacts may have been responsible for decreasing the rate of variation of the coastline in certain time periods and sectors. The information obtained is of great value for the study of the coastal region in the municipality and, induce a continuation of this research, with more parameters (wind, rainfall, current, temperature) to be studied in order to have an increase in the data collection, aiming at studies to predict the dynamics of coastline variation, making possible the social and environmental importance of the study generated.